Gene Duplication and Transference of Function in the paleoAP3 Lineage of Floral Organ Identity Genes - Galimba, Kelsey D.; Martínez-Gómez, Jesús; Di Stilio, Verónica S. (Frontiers in Plant Science, 2018)
The floral organ identity gene APETALA3 (AP3) is a MADS-box transcription factor involved in stamen and petal identity that belongs to the B-class of the ABC model of flower development. Thalictrum (Ranunculaceae), an emerging model in the non-core eudicots, has AP3 homologs derived from both ancient and recent gene duplications. Prior work has shown that petals have been lost repeatedly and independently in Ranunculaceae in correlation with the loss of a specific AP3 paralog, and Thalictrum represents one of these instances. The main goal of this study was to conduct a functional analysis of the three AP3 orthologs present in Thalictrum thalictroides, representing the paleoAP3 gene lineage, to determine the degree of redundancy versus divergence after gene duplication. Because Thalictrum lacks petals, and has lost the petal-specific AP3, we also asked whether heterotopic expression of the remaining AP3 genes contributes to the partial transference of petal function to the first whorl found in insect-pollinated species. To address these questions, we undertook functional characterization by virus induced gene silencing, protein-protein interaction and binding site analyses. Our results illustrate partial redundancy among Thalictrum AP3s, with deep conservation of B-class function in stamen identity and a novel role in ectopic petaloidy of sepals. Certain aspects of petal function of the lost AP3 locus have apparently been transferred to the other paralogs. A novel result is that the protein products interact not only with each other, but also as homodimers. Evidence presented here also suggests that expression of the different ThtAP3 paralogs is tightly integrated, with an apparent disruption of B function homeostasis upon silencing of one of the paralogs that codes for a truncated protein. To explain this result, we propose two testable alternative scenarios: that the truncated protein is a dominant negative mutant or that there is a compensational response as part of a back-up circuit. The evidence for promiscuous protein-protein interactions via yeast-two-hybrid combined with the detection of AP3 specific binding motifs in all B-class gene promoters provide partial support for these hypotheses.